Extracorporeal Shockwave Therapy in Cardiology: Current Status and Future Perspectives - Islam, AKM Monwarul; Majumder, AAS (Cardiovascular Journal, 2012)
Management of end-stage coronary artery disease is often hopeless because of lack of evidence-based, uniformly effective, safe, and inexpensive treatment options. Gene- or stem-cell-based therapies are not yet ready for routine clinical use, and heart transplantation is seriously limited by the scarcity of organs. In this regard, extracorporeal shockwave therapy is emerging as a noninvasive means to treat refractory angina and heart failure. Shockwaves are a form of acoustic wave having very high amplitude, abrupt peaking and very short duration, capable of inducing neovascularization. A number of preclinical and clinical studies are in favour of its efficacy and safety. However, more robust evidence is needed before routine application is recommended. Larger, randomized, placebocontrolled trials will hopefully define its status in the armamentarium of mankind in the battle against the deadly disease in future. Keywords: Shockwave; angiogenesis; angina. DOI: http://dx.doi.org/10.3329/cardio.v4i1.9395 Cardiovasc. J. 2011; 4(1): 80-87